Detection of citrus leaf blotch virus using digoxigenin-labeled cDNA probes and RT-PCR - Galipienso, Luis; Vives, María C.; Navarro, Luis; Moreno, Pedro; Guerri, José (2017)
Citrus leaf blotch virus (CLBV) was detected by dot-blot hybridization (DBH), and tissue print hybridization (TPH) and by one-step RT-PCR in citrus plants growing both in the greenhouse and in the field. DBH with digoxigenin-labeled cDNA probes allowed CLBV detection in dsRNA-rich and total RNA preparations equivalent to 5 and 0.1 mg of infected tissue, respectively. DBH gave intense signals with RNA extracts from young bark, tender shoots and young leaves, whereas the best hybridization signals with TPH were obtained using tender shoots and young leaf petioles. One-step RT-PCR was 10-fold more sensitive than DBH and amplification was obtained with all infected tissues. CLBV was readily detected in young leaves of infected Eureka lemon, Marsh grapefruit, Nules clementine, Navelina orange and Nagami kumquat in the greenhouse, using either hybridization or RT-PCR, but not in leaves of Pineapple sweet orange. Detection in field trees was less consistent and was only achieved by RT-PCR and DBH. CLBV was detected by DBH and RT-PCR in different citrus varieties from several geographic areas showing bud union crease on trifoliate rootstocks, but not in neighbor trees with the same symptoms or in other varieties showing bud union crease on those rootstocks. Failure to detect CLBV in trees with bud union crease could be due to low virus titer or uneven distribution within the plant. Alternatively, a different agent could be involved in causing bud union crease.